Підходи до формування соціального пакета як сучасного інструменту мотивації працівників - Котова, Н.І.; Нікуліна, А.В. (Вісник економічної науки України, 2014)
Узагальнено підходи щодо сутності та формування соціального пакета як інструменту мотивації працівників. Надано пропозиції з удосконалення його структури, складових і змістовного наповнення. Визначено чинники, які негативно впливають на процес запровадження соціального пакета. Обобщены подходы к сущности и формированию социального пакета как инструмента мотивации работников. Даны предложения по совершенствованию его структуры, составляющих и содержательного наполнения. Определены факторы, негативно влияющие на процесс внедрения социального пакета. The article deals with the theoretical and practical issues of regulation of individual labor relations by providing social package as a tool for personnel motivation. The approaches to the definition of a social package and its structure are summarized. Given suggestions that structurally it should contain: the obligation of the employer to implement legislative and provide additional benefits and guarantees social and labor issues, providing concrete examples of relevant personnel; duties of the employee to fulfill the requirements in the workplace, which is not only established by the legislation, but also put forward by the employer. The attention is focused on the factors that negatively affect the process of implementing a social package for Ukrainian companies, noted the absence of legal regulation and its spontaneity. The substantive content of the social package was justified, it is determined by the employer on the basis of the needs in attracting and retaining qualified personnel, promoting greater productivity, cost optimization staff. A new structure of social (motivational) package is defined. It includes the basic social guarantees stipulated by labor legislation and social security (basic component) and more material goods, the provision of which is carried outby the employer on his own initiative (enabling component). The mechanism with the definition of stages of the implementation of the social package and the basic principles of its formation was proposed.